Evaluation of a Highly Efficient DNA Extraction Method for Bacillus anthracis Endospores - Mandy Knüpfer; Peter Braun; Kathrin Baumann; Alexandra Rehn; Markus Antwerpen; Gregor Grass; and Roman Wölfel (Microorganisms, 2020)
A variety of methods have been established in order to optimize the accessibility of DNA originating from Bacillus anthracis cells and endospores to facilitate highly sensitive molecular diagnostics. However, most endospore lysis techniques have not been evaluated in respect to their quantitative proficiencies. Here, we started by systematically assessing the efficiencies of 20 DNA extraction kits for vegetative B. anthracis cells. Of these, the Epicentre MasterPure kit gave the best DNA yields and quality suitable for further genomic analysis. Yet, none of the kits tested were able to extract reasonable quantities of DNA from cores of the endospores. Thus, we developed a mechanical endospore lysis protocol, facilitating the extraction of high-quality DNA. Transmission electron microscopy or the labelling of spores with the indicator dye propidium monoazide was utilized to assess lysis efficiency. Finally, the yield and quality of genomic spore DNA were quantified by PCR and they were found to be dependent on lysis matrix composition, instrumental parameters, and the method used for subsequent DNA purification. Our final standardized lysis and DNA extraction protocol allows for the quantitative detection of low levels (<50 CFU/mL) of B. anthracis endospores and it is suitable for direct quantification, even under resource-limited field conditions, where culturing is not an option.